The Neural Crest as the First Production Site of the Erythroid Growth Factor Erythropoietin - Hirano, Ikuo; Suzuki, Norio (Frontiers in Cell and Developmental Biology, 2019)
While the neural crest is considered the fourth germ layer that originates a variety of tissues during mammalian development, we recently discovered that some neural crest cells and neuroepithelial cells play a unique role in secreting a vital hematopoietic hormone, erythropoietin (EPO), in mouse embryos. EPO production by the neural crest is transient in mid-stage embryos but essential for the first erythropoiesis in the yolk sac and for sufficient oxygen supply in the whole embryo growing in utero. The site of EPO production shifts from the neural crest to the liver in late embryonic stages, followed by interstitial fibroblasts of the kidneys in adults. Interestingly, the transition of EPO production sites synchronizes with the transition of erythropoietic sites during mouse development from the yolk sac and the fetal liver to the bone marrow. EPO produced by the neural crest and the neuroepithelium is first stored around the production sites and delivered to the yolk sac as an endocrine hormone for erythropoiesis after heartbeat activation. The fact that EPO is produced by some human cell lines derived from neuroblastoma, which mainly originates from the neural crest, provides evidence that the neural crest secretes EPO for primitive erythropoiesis not only in mouse but also in human embryos. Here, we introduce and discuss recent progress in studies on the mechanism of EPO production by the neural crest and its roles in erythropoietic development and in the fate of EPO-producing neural crest cells.